2020
DOI: 10.36380/scil.2020.wvj6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Foot and Mouth Disease in Cattle and Buffaloes in Different Governorates of Egypt.

Abstract: Foot and Mouth Disease (FMD) is highly contagious disease affected cloven-hoofed animals which result in substantial economic losses. The present study was aimed to detect FMDV by different serological and molecular methods in cattle and buffaloes for providing an accurate and rapid diagnosis of FMD disease. 86 samples of tongue epithelium biopsies, fluid vesicles samples and saliva, as well as 86 coagulated and uncoagulated blood samples, were collected from 64 and 22 suspected cattle and buffaloes respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Differentiating between these two categories of animals is important during serological surveys to detect evidence of infection in vaccinated animals [17]. Lower results of FMD detection were reported by El-Rhman et al [11] and a nearly similar result was reported by Salem et al [18], while higher results were reported by Ibrahim1 et al [19] and Zeedan et al [20] who used FMD-3ABC to distinguish FMDV-infected or carrier animals from vaccinated animals in Egypt.…”
Section: Discussionmentioning
confidence: 92%
“…Differentiating between these two categories of animals is important during serological surveys to detect evidence of infection in vaccinated animals [17]. Lower results of FMD detection were reported by El-Rhman et al [11] and a nearly similar result was reported by Salem et al [18], while higher results were reported by Ibrahim1 et al [19] and Zeedan et al [20] who used FMD-3ABC to distinguish FMDV-infected or carrier animals from vaccinated animals in Egypt.…”
Section: Discussionmentioning
confidence: 92%
“…FMD is endemic in Egypt with three distinct serotypes O, A, and SAT 2 (69,70). It was reported for the first time in 1950 by the World Reference Laboratory for Foot and Mouth Disease.…”
Section: Egyptmentioning
confidence: 99%
“…FMDV strains O, A, and SAT-2 were commonly affecting buffalos and cattle in different Egyptian governorates at a period in the summer of 2017. FMDV is transboundary from neighbor countries or thorough the importation of carrier animals (Zeedan et al 2020).…”
Section: Introductionmentioning
confidence: 99%